2005
DOI: 10.1109/tac.2005.847038
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of oscillations through backstepping in high-dimensional systems

Abstract: This paper introduces a method for obtaining stable and robust self-sustained oscillations in a class of single input nonlinear systems of dimension n ≥ 2. The oscillations are associated to a limit cycle that is produced in a second-order subsystem by means of an appropriate feedback law. Then, the controller is extended to the full system by a backstepping procedure. It is shown that the closed-loop system turns out to be generalized Hamiltonian and that the limit cycle can be thought as born in a Hopf bifur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…Based on [50,51]), it is suggested that the limit cycle is related with the Lyapunov function. That is, having an admissible limit cycle, the Lyapunov function can be proposed as…”
Section: Proposed Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on [50,51]), it is suggested that the limit cycle is related with the Lyapunov function. That is, having an admissible limit cycle, the Lyapunov function can be proposed as…”
Section: Proposed Solutionmentioning
confidence: 99%
“…Inspired by this motion-planning method, a similar approach was developed in [41] for a class of single-input nonlinear systems of arbitrary dimension with a cascade-based structure, this time with a backstepping procedure applied to extend the robust oscillatory behavior of a controlled system involving the first two states to the full-order system (the methodology is illustrated with the control of a third-order model of a magnetic levitation ball system). The same backstepping-based procedure is applied in [42] for the control of oscillations in DC-AC converters modeled in linear terms, and an adapted version is applied in [43] for the control of a nonlinear mathematical model of a DC-AC boost converter.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a local Lyapunov function for the closed-loop system can be computed using V = (Hω), with ω given by (24), if the anti-exact part ω 0,a = H dω vanishes only at the origin.…”
Section: Theorem 32mentioning
confidence: 99%
“…Application of stabilization using first integrals of mass-action systems (and more generally positive systems) was presented in [23]. Stabilization of periodic orbits was also considered in [24] using backstepping.…”
Section: Stabilization To a Periodic Orbit By Dampingmentioning
confidence: 99%
“…If a control law is able to produce such a limit cycle, the generation of alternating current will be accomplished without the need for introducing any time dependent reference signal (tracking method). The generation of limit cycles for producing self-oscillations has been successfully applied to electro-mechanical systems Gómez-Estern et al, 2002;Gordillo et al, 2002;Aracil et al, 2004). In this idea was used to generate oscillations in a three-phase DC/AC converter, which was modelled using a linear model.…”
Section: Introductionmentioning
confidence: 99%